2021
DOI: 10.7759/cureus.15795
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Omental Bleeding Treated by Laparoscopic Partial Omentectomy: A Case Report and Review of the Literature

Abstract: Omental bleeding is potentially life-threatening. There are many causes of omental bleeding including trauma, neoplasia, arterial aneurysm rupture, omental torsion, vasculitis, or segmental arterial mediolysis (SAM). Without remarkable pathological features, the diagnosis of idiopathic omental bleeding is made. Omental bleeding is relatively a rare disease, and there is no established treatment strategy.A 53-year-old woman was brought to the ED for sudden onset abdominal pain. CT revealed hematoma in the oment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Early diagnosis and definitive management are of a paramount importance in achieving favourable patient’s outcome. There are many causes of omental bleeding which includes trauma, neoplasia, anticoagulant medications, spontaneous arterial aneurysmal or pseudoaneurysmal rupture, omental torsion, vasculitis, and segmental arterial mediolysis [ 5 ]. Omental artery pseudoaneurysm is scarcely documented in the literature with a higher prevalence seen in men compared to women with a ratio of 6:1 and age of onset ranging widely from 20s to 80s [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early diagnosis and definitive management are of a paramount importance in achieving favourable patient’s outcome. There are many causes of omental bleeding which includes trauma, neoplasia, anticoagulant medications, spontaneous arterial aneurysmal or pseudoaneurysmal rupture, omental torsion, vasculitis, and segmental arterial mediolysis [ 5 ]. Omental artery pseudoaneurysm is scarcely documented in the literature with a higher prevalence seen in men compared to women with a ratio of 6:1 and age of onset ranging widely from 20s to 80s [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the uncommon nature of this disease there are no specific recommendations for treatment. A recent literature review [ 5 ] found only 25 cases of omental bleeding in the literature, with varied management from transcatheter arterial embolization (TAE), laparotomy, or laparoscopy with omentectomy or simple ligation of the bleeding artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A brief review on PubMed yields 14 pertinent English‐language publications containing “idiopathic omental hemorrhage,” all of which are case reports. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 The majority of patients are male, aged 20–65, presenting with abdominal pain of varied locations and duration ranging from hours to days. Few patients had predisposing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of omental bleeding consists of laparotomy, laparoscopy, or TAE [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ].…”
Section: Discussionmentioning
confidence: 99%